2023
DOI: 10.7759/cureus.40729
|View full text |Cite
|
Sign up to set email alerts
|

Using the Evidence-Development-Validation-Consensus (EDVC) Approach to Develop and Validate maxSIMdrone: A Training Program for Healthcare Professionals to Provide Cardiac Arrest Care Using Drones

Abstract: The challenges of delivering cardiac arrest (CA) courses in rural and remote (R&R) locations worldwide have been further exacerbated by the COVID-19 pandemic. However, it is important to note that this problem has always existed. The implementation of social distancing measures to combat the pandemic has had a significant impact on healthcare and medical education, particularly in relation to the training of students, laypeople (LP), and healthcare professionals (HCPs) in CA care. The combination of pandemic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A UAV was launched with a simulation scenario to train healthcare workers in AED operation and direct lay people in safe use with basic life support protocols (32). A literature review showed that different training methods yielded similar outcomes.…”
Section: Discussion Of Literature Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A UAV was launched with a simulation scenario to train healthcare workers in AED operation and direct lay people in safe use with basic life support protocols (32). A literature review showed that different training methods yielded similar outcomes.…”
Section: Discussion Of Literature Datamentioning
confidence: 99%
“…A literature review showed that different training methods yielded similar outcomes. The authors postulated that a comprehensive training program related to UAVs should include cognitive, affective, and psychomotor aspects, addressing different skills and knowledge areas (32).…”
Section: Discussion Of Literature Datamentioning
confidence: 99%